Criminal liability of drugs for elimination: what the dentist should know - Коваль, О. І.; Коваль, П. Б.; Біденко, Н. В. (Actual Dentistry, 2019)
Resume. The article presents the laws of the Criminal Code of Ukraine, which regulate the responsibility of medical staff for non-fulfillment or improper performance of their duties. Key words: the Criminal Code, official authority, rights of medical staff, responsibilities of medical staff.